Robot-assisted epiretinal membrane peeling: a prospective assessment of pre- and intra-operative times and of surgeons’ subjective perceptions - Turgut, Ferhat; Somfai, Gábor Márk; Heussen, Florian M.; Eberle, Alexander; de Smet, Marc D.; Becker, Matthias D. (Journal of Clinical Medicine, 2023)
Purpose: The Preceyes Surgical System (PSS) is a robotic assistive device that may enhance surgical precision. This study assessed pre- and intra-operative times and surgeons’ perceptions of robot-assisted epiretinal membrane peeling (RA-MP). Methods: We analyzed the time requirement of three main tasks: the preparation of the PSS (I), patient preparation (II), and surgery (III). Following surgery, the surgeons were asked questions about their experience. Results: RA-MP was performed in nine eyes of nine patients. Task I required an average time of 12.3 min, initially taking 15 min but decreasing to 6 min in the last surgery. Task II showed a mean time of 47.2 (range of 36-65) min. Task III had a mean time of 72.4 (range of 57-100) min. A mean time of 27.9 (range of 9-46) min was necessary for RA-MP. The responses to the questionnaire revealed a trend towards increasing ease and reduced stress as familiarity with the PSS increased. Conclusions: A substantial reduction in pre- and intra-operative times, decreasing to a total of 115 min, was demonstrated. RA-MP was positively anticipated by the surgeons and led to no hand or arm strain while being more complex than manual MP.
Gesehen am 15.11.2023